γ-Ray and ultra-high energy neutrino background suppression due to solar radiation - Shyam Balaji (Physics Letters B, 2023)
The Sun emits copious amounts of photons and neutrinos in an approximately spatially isotropic distribution. Diffuse γ-rays and ultra-high energy (UHE) neutrinos from extragalactic sources may subsequently interact and annihilate with the emitted solar photons and neutrinos respectively. This will in turn induce an anisotropy in the cosmic ray (CR) background due to attenuation of the γ-ray and UHE neutrino flux by the solar radiation. Measuring this reduction, therefore, presents a simple and powerful astrophysical probe of electroweak interactions. In this letter we compute such anisotropies, which at the Earth (Sun) can be at least ≃5×10−3(1)% and ≃1×10−16(2×10−14)% for TeV scale γ-rays and PeV scale UHE neutrinos respectively. We briefly discuss observational prospects for experiments such as the Fermi Gamma-Ray Space Telescope Large Area Telescope (Fermi LAT), High-Altitude Water Cherenkov (HAWC) detector, The Large High Altitude Air Shower Observatory (LHAASO), Cherenkov Telescope Array (CTA) and IceCube. The potential for measuring γ-ray attenuation at orbital locations of other active satellites such as the Parker Solar Probe and James Webb Space Telescope (JWST) is also explored.